RETRACTED ARTICLE: GREM2 maintains stem cell-like phenotypes in gastric cancer cells by regulating the JNK signaling pathway. Issue 19 (2nd October 2019) - Ran, Ao; Guan, Lin; Wang, Jiani; Wang, Ying
Statement of Retraction: We, the Editors and Publisher of the journal  Cell Cycle, have retracted the following article: Ao Ran, Lin Guan, Jiani Wang, and Ying Wang. GREM2 maintains stem cell-like phenotypes in gastric cancer cells by regulating the JNK signaling pathway. Cell Cycle. 2019;18(19):2414–2431. doi: 10.1080/15384101.2019.1646561 Since publication, significant concerns have been raised about the integrity of the data and reported results in the article. When approached for an explanation, the authors did not provide their original data or any necessary supporting information. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article. The corresponding author listed in this publication has been informed. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.